Letramentos acadêmicos e as dinâmicas de produção e circulação do conhecimento em um programa de pós-graduação de excelência - Paula Aparecida Diniz Gomides (2023)
The perspective of Academic Literacies emerges in line with New Literacy Studies, considering that literacies are developed throughout engagement in social practices, contextualized and in the midst of power relations. We understand that the link to programs recognized as Excellence, evaluated by CAPES as Programs that have achieved international status, implies the development of certain academic literacy practices related to the production and circulation of knowledge whose nature derives from the greater stimulus to the internationalization of universities. As a result, engaging in situations that include international research partnerships, taking classes in foreign languages and participating in events abroad, for example, are activities in which professors linked to courses of excellence potentially become involved. Our main objective is to analyze the academic trajectories of professors regarding social literacy practices in different areas of knowledge in a graduate program rated as excellent. Intending to go deeper into literacy practices, we carried out a qualitative research, inspired by ethnography and based on semi-structured interviews. We interviewed and accompanied four professors accredited to a Graduate Program in Education of excellence in the fields of Biology, Pedagogy, Sociology and Physical Education, focusing on different institutional generations and gender profiles. We were interested in the different meanings constructed throughout accreditation in the Program, as well as the academic trajectory and the constitution of academic literacies throughout social practices and frameworks related to different roles adopted in this connection with the Program. The official documents that guide a Brazilian Postgraduate evaluation policy dictate certain social practices, the expectation of which mobilizes resources to achieve this status. We identified multiple identities, in view of the different expectations resulting from academic affiliation, the impact of academic trajectories of professors linked to these Programs, in the academic literacies practices in which they engage and the re-signification of these literacies, influenced by the internationalization policy of Graduate programs.